PENGELOLAAN KESAN KOMIKA STAND UP COMEDY PADA KOMUNITAS STAND UP INDO PEKANBARU - Denny Aprianto Vijay Lubis; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Stand up comedy has become a new interest in the world of art, especially comedy in Indonesia. Stand up comedy gives freedom to the person to talk about and do anything, so that a comic has his own way to make the audience interested and entertained. This study aims to determine the front stage, middle stage, and back stage comic in Pekanbaru city. This study uses qualitative research methods using dramaturgy studies. The informant of the study consisted of six people, consisting of three main informants and three supporting informants. Data collection techniques are conducted by interview, observation, and documentation. Data analysis techniques use the Miles and Huberman interactive models in the form of data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that the appearance of a comic when on stage is the result of managing an impression that is designed in such a way as to the demands of the profession being pursued. Front stage is a display full of settings. An ideal concept that someone wants to display in accordance with the expectations of society. As a stand up comedian, the comic look for a